2016
DOI: 10.1017/s1463423616000244
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the patient evaluation scale (PES) for primary health care in Nigeria

Abstract: The PES and PES-SF contain items that are relevant to the needs of patients in Nigeria. The good measurement properties of the questionnaire demonstrates its potential usefulness for patient-focussed quality improvement activities in Nigeria. There is still need to translate these questionnaires into major languages in Nigeria and assess their validity against external quality criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Thirteen studies24–36 addressed eight nationally validated PC performance instruments—namely the South African and Malawian versions of the Primary Care Assessment Tool (ZA PCAT and PCAT-Mw respectively)26 34; the electronic Tool to Improve Quality of Healthcare (e-TIQH) in Tanzania25; the Nigerian Patient Evaluation Scale (PES)31; the South African Ideal Clinic Realisation and Maintenance (ICRM) instrument29; SafeCare Essentials tool33; the European Task Force for Patient Evaluation of General Practice (EUROPEP)37; and the Client Satisfaction Survey Questionnaire 35. (Information on instruments is summarised in Appendix D uploaded as a supplementary file.)…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies24–36 addressed eight nationally validated PC performance instruments—namely the South African and Malawian versions of the Primary Care Assessment Tool (ZA PCAT and PCAT-Mw respectively)26 34; the electronic Tool to Improve Quality of Healthcare (e-TIQH) in Tanzania25; the Nigerian Patient Evaluation Scale (PES)31; the South African Ideal Clinic Realisation and Maintenance (ICRM) instrument29; SafeCare Essentials tool33; the European Task Force for Patient Evaluation of General Practice (EUROPEP)37; and the Client Satisfaction Survey Questionnaire 35. (Information on instruments is summarised in Appendix D uploaded as a supplementary file.)…”
Section: Resultsmentioning
confidence: 99%
“…Two recent meta-analyses of case-control studies demonstrated that circulating adiponectin levels could be signi cantly higher in the RA patients than those in the health controls [30,31]. However, it was also reported separately that adiponectin levels were not related to RA activity [30,32]. Meanwhile, the ndings from meta-analyses consistently indicated that patients with RA may have higher circulating leptin levels compared with the control group [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the importance of the orientation of PHC team members to the type of service that the PHC team is providing. This second theme, which recognises that the organisation of primary care is critical to issues of acceptability and access, is also addressed in the papers by Ogaji et al (2017), Wang and Liang (2017), Chang et al (2017) and Ward (2017).…”
mentioning
confidence: 98%
“…In a study undertaken by an international team drawn from the Universities of Port Harcourt and Manchester, Ogaji et al (2017) describe the lack of applicable tools to measure patient evaluations of primary care in sub-Saharan Africa. Drawing on a systematic review and patient interviews they describe in detail the development and validation of a patient evaluation tool and a short form of the tool.…”
mentioning
confidence: 99%
See 1 more Smart Citation